ANTIBACTERIAL SUSCEPTIBILITY PROFILES OF COLIFORMS ISOLATED FROM BOVINE SUBCLINICAL AND CLINICAL MASTITIS AGAINST FLUOROQUINOLONES - K. Saranya; S. Pavulraj; L. Kalaiselvi; S. Amsaveni; S. Ramesh (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The primary objective of this study was to assess the antibacterial sensitivity pattern of Coliforms isolates from clinical and sub-clinical mastitis to quinolones. Forty coliforms isolates from bovine clinical and subclinical mastitis were tested for antimicrobial susceptibility by measuring MIC by Resazurin dye broth microdilution method. Of the 27 E. coli isolates tested, only 7.4% of the isolates were found to be susceptible to ofloxacin and 7.37, 55.55 and 59.25% of isolates were found to be resistant to ciprofloxacin, enrofloxacin and ofloxacin, respectively. The proportion of coliform isolates other than E. coli resistant to fluoroquinolones tested were 30-47%. The result of this study indicates the presence of high level of resistance of coliforms against fluoroquinolones. This necessitates routine monitoring of resistance pattern among field isolates of mastitis and to develop suitable antimicrobial usage policy.